EMPLOYEE PERFORMANCE BASED ON WORK STRESS AND JOB SATISFACTION AT PT ASURANSI JIWA MANULIFE INDONESIA TELEMARKETING DIVISION SOUTH TANGERANG BRANCH - Ading Sunarto; Nindie Ellesia (Yayasan Education and Social Center, 2022)
This study aims to determine the partial and simultaneous influence of job stress and job satisfaction on employee performance at PT Asuransi Jiwa Manulife Indonesia, Telemarketing Division, South Tangerang Branch. The research method used in this research is descriptive quantitative. This study took the population of all employees at PT. Manulife Indonesia Life Insurance Telemarketing Division, South Tangerang Branch, totaled 57 people, while the sample used was the saturated sample formula. The research variable consists of independent or independent variables (X), job stress (X1), and Job satisfaction (X2), while the dependent or dependent variable (Y) is performance. The data collection method is through questionnaires distributed to employees of the telemarketing division of PT Asuransi Jiwa Manulife Indonesia. South Tangerang branch, the data obtained were then processed using the SPSS version 25.0 application. The analysis technique used is the multiple linear regression analysis models. And using the instrument test, hypothesis testing, which includes classical assumption test, t-test, F test, and coefficient of determination. The results of testing the effect of work stress and job satisfaction affect employee performance. Based on the results of the SPSS calculation, it is obtained that the Fcount = 29.185 with a significant F value of 0.000. Using a significant level of 0.05, the table value with DK = n-k-1 (57-2-1 = 54) obtained a Ftable of 3.17 significant level of 0.000. The significance value is still below the set significance value of 0.05, so it can conclude that work stress and Job satisfaction significantly affect employee performance with the regression line equation. Y = 2.709 + 0.198X1 + 0.542X2